BUSINESS INTELLIGENCE, ANALYTICS, AND DATA SCIENCE A MANERIAL PERSPECTIVE - SHARDA RAMESH; DURSUN DELEN; EFRAIM TURBAN; DAVID KING (NOIDA PEARSON INDIA EDUCATION SERVICES PVT LTD, 2025)
"Business Intelligence, Analytics, and Data Science" by Ramesh Sharda, often co-authored with Dursun Delen and Efraim Turban, is a comprehensive textbook that provides a managerial perspective on how organizations can leverage data to gain insights and make better decisions. It's a widely used resource in academic and professional settings for understanding the interwoven concepts of business intelligence (BI), data analytics
DATA SCIENCE
Keywords: DATA ANALYTICS; MANAGEMENT